REKAYASA WEB UNTUK PEMESANAN HANDPHONE BERBASIS JQUERY PADA PERMATA CELL - Indra Warman; Atma Zahni (Jurnal Momentum ISSN 1693-752X)
Information technology is now increasingly prevalent in many areas and can not be avoided. The use of technology has become the main requirement to support the quality of the field and become the most important capital in a company ahead of the competition. One form of this competition is to improve customer service. Problems encountered in serving consumers to order. To improve and facilitate the service to consumers would require a web information system. Overcoming it is then designed a web-based order system. The purpose of this study is to design a web. This web makes it easy for the customer in terms of, the cost and time as well as helped the store to serve the consumer ordering. Based on the study, expected to improve the effectiveness, efficiency of the stores in serving consumers.